2021
DOI: 10.1038/s41598-021-89004-x
|View full text |Cite
|
Sign up to set email alerts
|

Highly specific and ultrasensitive plasma test detects Abeta(1–42) and Abeta(1–40) in Alzheimer’s disease

Abstract: Plasma biomarkers that reflect specific amyloid beta (Abeta) proteoforms provide an insight in the treatment effects of Alzheimer’s disease (AD) therapies. Our aim was to develop and validate ready-to-use Simoa ‘Amyblood’ assays that measure full length Abeta1-42 and Abeta1-40 and compare their performance with two commercial assays. Linearity, intra- and inter-assay %CV were compared between Amyblood, Quanterix Simoa triplex, and Euroimmun ELISA. Sensitivity and selectivity were assessed for Amyblood and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…Furthermore, several studies reported similar findings comparing enzyme‐linked immunosorbent assays and Simoa platforms for plasma Aβ40 and Aβ42. 7 , 14 , 15 Spearman coefficients were 0.68 and 0.71 for, respectively, Aβ40 and Aβ42, which corroborates the findings in this article for the same assays. Since completion of this study, many of the methods have undergone additional refinement and new method comparison studies are underway.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, several studies reported similar findings comparing enzyme‐linked immunosorbent assays and Simoa platforms for plasma Aβ40 and Aβ42. 7 , 14 , 15 Spearman coefficients were 0.68 and 0.71 for, respectively, Aβ40 and Aβ42, which corroborates the findings in this article for the same assays. Since completion of this study, many of the methods have undergone additional refinement and new method comparison studies are underway.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the discovery and validation of AD bloodbased biomarkers, made possible with the development of novel techniques (e.g. immunoprecipitation-mass spectrometry or the high-precision immunoassays) [23,25,[99][100][101] will offer major opportunities for screening and enrollment of potential participants for primary and secondary prevention trials, reducing trial duration and costs due to screen failures.…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as we know, blood-based Aβ assay technologies using ELISA and mass spectrometry demonstrate LoD values in the hundreds of pg/mL ( Sehlin et al, 2010 ; Oeckl and Otto, 2019 ). In addition, recent studies related to blood-based AD diagnosis have reported that digital ELISA technology, or the single molecule assay (SIMOA), can detect specific N-terminal Aβ peptides in plasma with high accuracy ( De Meyer et al, 2020 ; Thijssen et al, 2021 ). Immunomagnetic reduction (IMR) technology has also been introduced as a promising blood-based biomarker platform to diagnose AD at early stages ( Yang et al, 2017 ; Lue et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%